Modelo de gestión operativa para la junta administradora de agua potable y saneamiento San José de Ayora. - Hidalgo, Jairo S. (2021)
This research work was carried out at the San José de Ayora drinking water and sanitation administration board (Junta de Alcantarillado, Agua Potable y SaneamientoJAAPS). It is located in the Cayambe canton of the province of Pichincha. The study developed an operational management model for the institution. The research started from gathering information on the current situation of the institution and useful bibliographic material. Then, creating a manual of functions and elaborating a graphical representation of the macro-processes that JAAPS carries out. Once the information was found, we proceeded to interview the directors of the institution as well as the workers in the operational area, in order to develop the schemes of the macro-processes which are the following: - Water processing. - Collection of garbage or solid waste. - Public purchase. - Billing and collection for services After that, we started the elaboration of the manual of functions of the operational area of JAAPS, starting from the design of an organization chart, to later elaborate a manual of functions for the existing positions in the organization, which are: - Collector - Accounting assistant - Plant manager - Water operators - Solid waste operators. - Driver - Accountant In addition, we recommended creating an additional position that should be in charge of the administration, organization and direction of JAAPS to achieve the organization's objectives regardless of the directive in office.